2009
DOI: 10.1007/s10456-009-9134-8
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the anti-angiogenic effects of DNA-damaging and cytoskeletal-disrupting agents

Abstract: The discovery of molecules with anti-angiogenic properties has led to promising new strategies for the treatment of diseases characterized by excessive new vessel growth, such as cancer and haemangioma. We have assessed the effects of DNA-damaging and cytoskeletal-disrupting agents in vitro on several endothelial cell functions. We report that bleomycin, mitomycin C and cytoskeletal-disrupting drugs (2-methoxyestradiol, taxol, vincristine, vinblastine, colchicine, nocodazole, and cytochalasin D) exhibit anti-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 21 publications
6
33
0
Order By: Relevance
“…It induces endothelial cell apoptosis and is also a potent inhibitor of endothelial cell growth, migration, and in vitro capillary-like tube formation. 248 Given that endothelial cells also possess a high tubulin content, a biological rationale for IH sensitivity to vincristine exists. 249 Most reports on the efficacy of vincristine address the treatment of patients with vascular lesions that were not true IHs but rather KHE or TAs associated with KMP.…”
Section: Vincristinementioning
confidence: 99%
“…It induces endothelial cell apoptosis and is also a potent inhibitor of endothelial cell growth, migration, and in vitro capillary-like tube formation. 248 Given that endothelial cells also possess a high tubulin content, a biological rationale for IH sensitivity to vincristine exists. 249 Most reports on the efficacy of vincristine address the treatment of patients with vascular lesions that were not true IHs but rather KHE or TAs associated with KMP.…”
Section: Vincristinementioning
confidence: 99%
“…38 In addition, nocodazole exhibits anti-angiogenic effects in vitro along with potent inhibitory effects on endothelial growth. 39 Taxol (paclitaxel), an agent that stabilizes microtubules, facilitates microtubule polymerization and increases cell stiffness and viscosity. 40 Taxol has been actively investigated for its anti-angiogenic effects both in vitro and in vivo.…”
Section: Microtubule-targeting Moleculesmentioning
confidence: 99%
“…This is corroborated by the observation that bleomycin inhibits growth factor-induced endothelial cell invasion, endothelial cell growth and migration, and also induces endothelial cell apoptosis (Mabeta and Pepper, 2009).…”
Section: Bleomycinmentioning
confidence: 53%
“…In a study using the CAM assay, vincristine had an inhibitory effect on vascularisation. The drug is also a potent inhibitor of endothelial cell growth, migration and in vitro capillary-like tube formation, and induces endothelial cell apoptosis (Mabeta and Pepper, 2009). Only a few studies have reported on the use of vincristine for the treatment of IH.…”
Section: Vincristinementioning
confidence: 99%